2014
DOI: 10.1016/j.childyouth.2013.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Implementing evidence-supported methods in residential care and special education: A process-model

Abstract: This article presents the findings of a qualitative study in a Flemish centre for children and adolescents with emotional and behavioural disorders. The change with regard to the demand for care of this highly troubled population has created a need for intervention models that address students' socio-emotional needs. When preparing an organization to implement such intervention models, it is critical to obtain a thorough needs assessment or pre-implementation evaluation of staff in the organization. Fifty inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This is supported by several authors (Bastiaanssen et al, 2014;Boone, 2012;Curby, Rimm-Kaufman & Abry, 2013;Soenen et al, 2014;Vargas, 2013). During the third phase it was indicated that these rules and boundaries should be clear and easily understandable.…”
Section: Structure Environment To Accommodate Specific Needsmentioning
confidence: 93%
See 2 more Smart Citations
“…This is supported by several authors (Bastiaanssen et al, 2014;Boone, 2012;Curby, Rimm-Kaufman & Abry, 2013;Soenen et al, 2014;Vargas, 2013). During the third phase it was indicated that these rules and boundaries should be clear and easily understandable.…”
Section: Structure Environment To Accommodate Specific Needsmentioning
confidence: 93%
“…He believes that MCSA may add to the trauma of these learners, which may result in even more emotional and behavioural difficulties. Several authors (Quisenberry & Foltz, 2013;Soenen, D'Oosterlinck & Broekaert, 2014) confirm that many children placed in clinic schools have experienced abuse. For the purpose of this study the focus is specifically on MCSA victims placed in a clinic school.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Traditionally, process models have been used to provide insight into improving organizational tenets, for example, to help build capacity in nonprofit sports organizations (Miller & Doherty, 2016). Other contexts in which process models have been employed include (a) exploring organizational components related to college counselors' referrals of students to other mental health providers (Iarussi & Shaw, 2016), (b) helping a center for children and youth with emotional and behavioral disorders effectively address the students' socioemotional needs (Soenen et al, 2014), (c) improving outcomes in substance abuse treatment centers (Lehman, Simpson, Knight, & Flynn, 2011), and (d) formulating successful partnerships with Spanish-speaking immigrant families within their communities (Gonzalez, 2017). In education specifically, a process approach is articulated by the multitiered system of supports (MTSS) framework that schools follow to provide targeted support to struggling students (Jimerson, Burns, & VanDerHeyden, 2007).…”
Section: Process Modelmentioning
confidence: 99%
“…This general and open definition is purposeful because these models can be offered in varying formats for creating visual representations of some process or relationship between variables or factors, including the process by which a program is planned, organized, and implemented (Damschroder & Hagedorn, 2011). For example, process models may contain visual representations of stages (Bryan & Henry, 2012) or mediating and moderating factors of relationships between multiple variables (Bøe et al, 2014); they may also represent bidirectional relationships between factors or variables (Soenen, D'Oosterlinck, & Broekaert, 2014), be cyclical in nature (Den Hamer, Konijn, & Keijer, 2014), or provide a multidirectional framework for describing a process of services (Iarussi & Shaw, 2016). One central difference between process models and logic models is that logic models explicitly establish the causal linkages that create change and delineate clearly how inputs and actions lead to specific outcomes.…”
mentioning
confidence: 99%